The Effect of Booklet Media on Increasing Mother’s Knowledge in Stunting Prevention - Pangaribuan, Ingka Kristina; Mutmainah, Jamiah; Dinda Sari, Artika; Rini, Ovel; Rachmat, Ade (Journal of Maternal and Child Health Sciences (JMCHS), 2022)
Background:Stunting is the most common form of malnutrition (PE/micronutrients), affecting before birth and early after birth, related to maternal size, nutrition during pregnancy, and fetal growth. Stunting is not only caused by one factor but is caused by many factors, and these factors are interrelated with one another. There are three main factors that cause stunting, namely unbalanced food intake, history of low birth weight (LBW) and history of disease. 3 Balanced food intake is related to the content of nutrients including carbohydrates, proteins, fats, minerals, and vitamins.Purpose: To find out the effect of booklet media on increasing maternal knowledge in preventing stunting and to find out the characteristics of mothers under five.Methods: This study uses a quasi-experimental research method (quasi-experimental). The design used is a one group pre-test and post-test design all mothers who have toddlers aged 0-5 years at the Simpang Tertitit Health Center, Bener Meriah Regency with 45 sample. Results There is an Effect of Media Booklet on Increasing Mother's Knowledge in Stunting Prevention at Simpang Teritit Health Center, Wih Pesam District, Bener Meriah Regency in 2022 with 45 respondents there is a significant relationship with a p value of 0.03